2007
DOI: 10.1634/stemcells.2006-0664
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and Differentiation to Hepatocyte‐Like Cells of Nonparenchymal Epithelial Cells from Adult Human Liver

Abstract: Activation and proliferation of human liver progenitor cells has been observed during acute and chronic liver diseases. Our goal was to investigate the presence of these putative progenitors in the liver of patients who underwent lobectomy for various reasons but did not show any hepatic insufficiency. Hepatic lesions were evaluated by histological analysis. Nonparenchymal epithelial (NPE) cells were isolated from samples of human liver resections located at a distance from the lesion that motivated the operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 61 publications
2
46
1
2
Order By: Relevance
“…Little is known about whether CD90/Thy-1, which has been described for adult hepatic progenitors in rodents, [63][64][65] characterizes human hepatic progenitors (as described in 1 case 50 ), although it is often not found in the human liver. 34,48,66 Nava et al 26 could not find CD90 in human fetal hepatic progenitors from the first trimester, but they did find it in cells from the second trimester that coexpressed CD90 and hepatic markers (as we found in low percentages for the late second trimester). In contrast, Fiegel et al 64 found CD90 expression during all stages of rat liver development but at higher levels only in the early developmental stages.…”
Section: Discussioncontrasting
confidence: 46%
“…Little is known about whether CD90/Thy-1, which has been described for adult hepatic progenitors in rodents, [63][64][65] characterizes human hepatic progenitors (as described in 1 case 50 ), although it is often not found in the human liver. 34,48,66 Nava et al 26 could not find CD90 in human fetal hepatic progenitors from the first trimester, but they did find it in cells from the second trimester that coexpressed CD90 and hepatic markers (as we found in low percentages for the late second trimester). In contrast, Fiegel et al 64 found CD90 expression during all stages of rat liver development but at higher levels only in the early developmental stages.…”
Section: Discussioncontrasting
confidence: 46%
“…We first cultivated epithelial progenitor cells under selective conditions (17) and obtained clusters with a typical morphology that lasted for more than two months. After evaluating a large panel of markers because no single antigen had been definitely validated (30), we observed that all of the cultured cells expressed the a6 and b1 integrins, fundamental in ensuring cell adhesion and clonality of hepatic progenitor cells (1,2).…”
Section: Discussionmentioning
confidence: 99%
“…Media were changed three times a week. LEnPCs and L-EpPCs were counted at each passage and, at the first and fifth passages, characterized for the expression of various markers (1,2,16,17,(19)(20)(21).…”
Section: In Vitro Cell Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation, expansion and differentiation of adult HPCs to functional hepatocytes has been described by several workers [30,31,32], however identification of a specific marker of HPCs still remains a challenge. Clinical studies on the repopulation of the human liver by HPCs are still awaited.…”
Section: Hpc's and Fetal Liver Cells (Hepatoblasts)mentioning
confidence: 99%